Implementasi Program Mindful Parenting sebagai Upaya Pendampingan Perkembangan Bahasa pada Anak Speech Delay - Rusmiyati, Rusmiyati; Patilima, Hamid (Jurnal Pendidikan Kebutuhan Khusus, 2025)
This study aims to describe parents' understanding of the concept of mindful parenting in parenting, program implementation, its impact on interactions with children, to obstacles and supporting factors in its implementation. This study uses a qualitative method with a single case study type. The research participants consisted of 3 parents, 3 speech delay students, the principal and teachers. Data collection by observation, interviews, and document studies. After participating in the mindful parenting program, parents recognized that full presence, patience, and emotional regulation are essential in supporting children's communication development. The parents’ level of understanding of the program reached an average score of 80%, categorized as “Good”, obtained through the analysis of observation results using a 1-5 rating scale instrument. The program was implemented through: (a) parenting seminars, (b) haflah akhirussanah, (c) psychological tests, (d) home visits, and (e) additional study hours after school for students with speech delay. The findings indicate that the mindful parenting program has a positive impact on parental involvement and the development of communication in children with speech delay. The implication is that early childhood teachers and family counselors are encouraged to apply mindfulness-based interventions to strengthen collaboration with parents in supporting children’s language development.